Efficient electromagnetic energy harvester for railroad transportation. (August 2018) - Lin, Teng; Wang, John J.; Zuo, Lei
Abstract: An electromagnetic energy harvester is designed to produce electricity from rail track deflections induced by passing trains. Whereas typical existing vibration energy harvester technologies are built for low power applications of milliwatts range, the proposed harvester will be designed for higher power applications for major track-side equipment such as warning signals, wireless communications, track switches, track health monitoring systems, etc., which typically require a power supply ranging between several watts (continuous) to thousand watts (with intermittent duty cycle). Facing the challenge of large pulse vibrations on the track when trains pass by, a mechanical motion rectifier (MMR) with single shaft design is introduced to streamline the motion and force transmissions, by transforming bidirectional pulse vibrations into the unidirectional rotation at relatively steady speed. Bench tests indicate that 10–100 W of energy harvesting capability from train induced vibration and up to 74% efficiency. Simulations also indicate that the MMR mechanism can significantly increase the power output over the traditional harvesters while substantially reducing the average force amplitude under the same displacement input.